Fruit growth in cucumbers - Elfigih, Ahmed Taher, author; Workman, Milton, advisor; Basham, Charles W., committee member; Wood, Donald R., committee member (Colorado State University. Libraries, 1977)
A. Growth Differences Between Genetically Parthenocarpic Seeded (Pollinated) and Seedless (Not Pollinated) Fruits. Fruit growth in all cases was sigmoidal. The rate and duration of growth were essentially the same in both varieties and whether or not pollinated. Genetically parthenocarpic cultivars produced less fresh fruit weight when pollinated than when not pollinated, but the t-test showed the differences to be non-significant. B. Growth Differences Between Genetically Short- and Long-Fruited Lines and Varieties. Growth in all types was again sigmoidal. The long- and short-fruited types grew at essentially the same rate but for different durations. Overall correlation between ovary length at blooming and mature fruit length for long, medium and short-fruited cucumber was 0.97. This suggests that long-fruit ed types will have longer ovaries. No cell division occurred in ovaries after pollination. This suggests that cell division ceases at or shortly after anthesis and the subsequent fruit growth is due to cell enlargement rather than cell number. The analysis of variance for cell size and cell number in mature fruits of long-, medium- and short-fruited varieties showed highly significant differences between varieties between regions and their interaction. An inverse relationship existed between cell volume and cell number; cell volume increased toward the inner part of the fruit in all types. Differences in fruit size are usually due to differences in both cell number and cell size.
Covers not scanned.
Keywords: Cucumbers; Growth (Plants)